Fluorescently probing site-specific and self-catalyzed DNA depurination. Issue 19 (4th September 2019) - Fei, Yifan; Yan, Chenxiao; Yu, Yali; Gao, Longlong; Ye, Ting; Zhang, Qingqing; Gao, Heng; Zhou, Xiaoshun; Shao, Yong
Abstract : Self-catalyzed DNA depurination can be followed by a fluorescent probe to identify the SCD site and evaluate the depurination kinetics. Abstract : Depurination occurs via hydrolysis of the purine-deoxyribose glycosyl bond and causes nucleic acid damage. In particular, the DNA sequences that can undergo a self-catalyzed depurination (SCD) will cause a great uncertainty in duplicating, separating, purifying, and storing the DNA samples. Therefore, there is a great demand to develop a rapid detection method for SCD events. Herein, the use of a convenient fluorescence method to follow the site-specific SCD was demonstrated. We found that the resultant apurine site (AP site) from depurination can be selectively recognized by a fluorescent probe of palmatine (PAL) with a turn-on fluorescence response. The dependence of SCD on the bases of the depurination site, pH, metal ions, and time shows that our method can be used to rapidly evaluate the depurination process. Furthermore, the depurination process can be photo-switched using a photoacid as an external initiator. Our work will find wide applications in preliminarily identifying the DNA depurination.